The Emergence of Archaeology as Scientific Discipline - Ph. Subroto (Faculty of Cultural Sciences, Universitas Gadjah Mada, 1997)
It might be useful to mention of definition the archaeology, since the various definitions of Archaeology might reflect the emergence and the growth of archaeelogy itself. The word